Is current body temperature measurement practice fit-for-purpose?. (17th February 2021) - Machin, Graham; Brettle, David; Fleming, Susannah; Nutbrown, Rebecca; Simpson, Rob; Stevens, Richard; Tooley, Mark
Abstract: There has been a marked rise in the number of avoidable deaths in health services around the world. At the same time there has been a growing increase in antibiotic resistant so-called "superbugs." We examine here the potential role of body temperature measurement in these adverse trends. Electronic based thermometers have replaced traditional mercury (and other liquid-in-glass type) thermometers for reasons of safety rather than superiority. Electronic thermometers are in general less robust from a measurement perspective than their predecessors. We illustrate the implications of unreliable temperature measurement on the diagnosis and management of disease, including COVID-19, through statistical calculations. Since a return to mercury thermometers is both undesirable and impractical, we call for better governance in the current practice of clinical thermometry to ensure the traceability and long-term accuracy of electronic thermometers and discuss how this could be achieved.